Efeitos da tilápia do Nilo, Oreochromis niloticus, sobre a biomassa planctônica e a transparência da água ao longo de um gradiente de enriquecimento por nutrientes - Vasconcelos, Francisco Rivera (2010)
The omnivorous filter-feeding fish, Nile tilapia (Oreochromis niloticus), can have negative effects on water quality enhancing the eutrophication process. These effects depend on the nutrient enrichment level in the water. We carried out a mesocosm experiment for five weeks in a tropical man-made lake in Brazil to test ifthe effects of tilapias depend on of the level of nutrient enrichment. The experiment lasted for 5 weeks and a factorial 2x5 experimental design was used where the presence and absence of tilapias were manipulated in combination to 5 different levels of nutrient load in a total of 10 treatments. A two way repeated measure ANOVA was performed to evaluate the effects of time (t), tilapia (F), nutrients (NP) and the interactions among these factors on: chlorophyll a, water transparency, total phosphorous, total nitrogen, N:P ratio, zooplankton biomass and phytoplankton biovolume. The tilapia effect was evident, but nutrient enrichment didn t have any effect on the variables analyzed. Tilapia decreased the water transparency, total zooplankton biomass, calanoid copepod biomass, nauplii copepod biomass and cladocerans biomass. On the other hand, tilapia had no effect on phytoplankton biovolume. This lack of effect on phytoplankton is probably due to tilapia grazing that may counteract the positive effect of tilapia on phytoplankton via trophic cascades and nutrient recycling. Hence, a reduction in tilapia stock would not be an effective way to reduce phytoplankton biomass and improve water quality